Analysis of the Chemical Modification of Dental Enamel Submitted to 35% Hydrogen Peroxide "In-Office" Whitening, with or without Calcium - Rudá França Moreira; Fábio Pinheiro Santos; Estevão Antero Santos; Ramon Silva dos Santos; Marcelino José dos Anjos; Mauro Sayão de Miranda (Hindawi Limited, 2017)
Purpose. The purpose of this study was to evaluate changes in calcium and phosphorus content in dental enamel when subjected to "in-office" whitening for an extended time by using a 35% hydrogen peroxide solution, with and without calcium. Materials and Methods. 10 human teeth, from which the roots had been removed, were embedded in epoxy resin, and their surfaces were smoothed. The specimens were divided into two groups; in group 1, a whitening solution without calcium was used, while in group 2, the solution included calcium. Each specimen was evaluated at 6 different points before the bleaching treatment, and these points were reassessed after each session. A total of five sessions were carried out. Concentrations of calcium and phosphorus were measured by using the technique of X-ray fluorescence. Results. After performing a statistical analysis, it was found that there was no statistically significant loss of calcium and phosphorus during the whitening treatment, and the groups showed no statistical differences. Conclusion. Excessive use of hydrogen peroxide, with or without calcium, causes no loss of calcium and phosphorus.